Stressful intrapersonal and interpersonal experience of parents with Type 1 Diabetes Mellitus child - Mohd Nazori, Mohd Nazir (2023)
Background: Children mental health has been shown to be influenced by the parenting process and by the state of mental health of the parents. The experience of parents of children with Type 1 diabetes mellitus (T1DM) creates a unique and impactful environment to their parenting activities and mental state. This experience is less understood in the Malaysian context.